International Tuberculum Sellae Meningioma Study: Preoperative Grading Scale to Predict Outcomes and Inform Approach Selection. (16th November 2020) - Magill, Stephen T; Schwartz, Theodore H; Couldwell, William T; Gardner, Paul A; Heilman, Carl B; Sen, Chandra N; Akagami, Ryojo; Cappabianca, Paolo; Prevedello, Daniel M; McDermott, Michael W; ,
Abstract: INTRODUCTION: We published a grading scale for tuberculum sellae meningioma (TSM) using size, canal and artery involvement to predict post-operative visual and extent of resection (EOR) outcomes. METHODS: A 40-site retrospective study of TSM resected via transsphenoidal (TSA) or transcranial (TCA) approach was conducted (n = 947). Sites were divided into external validation/refinement (27 sites, n = 626 [66%]: n = 412 TCA [66%], n = 214 TSA [34%]) and validation cohorts (13 sites, n = 321 [34%]: n = 217 TCA [68%], n = 104 TSA [32%]). Multivariate logistic models were evaluated by AUC of ROC analysis and compared using a bootstrap method. Propensity matching was used to compare TSA/TCA outcomes. RESULTS: The published grading scale was significantly prognostic for visual outcome and EOR in the refinement cohort ( P  < .001). Refinement cohort data supported a simplified grading scale: tumor-score 1 (<17mm diameter) or 2 (³17mm diameter), canal-score 1 (no optic canal invasion) or 2 (any optic canal invasion), and artery-score 1 (abutting <180 degrees) or 2 (encasing arteries >180 degrees), which resulted in equivalent prognostic performance for vision ( P  = .08) and EOR (p = 0.55). The validation cohort validated the simplified scale for visual worsening (OR 1.69 per point increase, 95%CI 1.31-2.18, P  < .001) and EOR (OR 1.61 per point, 95%CI 1.38-1.88, P  < .001). The simplified scale remained independently prognostic after adjusting for clinical covariates including age, size, WHO grade and approach. After matching for simplified grading scale score, age, and size, rates of visual worsening were similar for TSA vs TCA (7.1% vs 9.0%, OR 0.78, 95%CI 0.44-1.38, p = 0.39), as was recurrence (HR 1.01, 95%CI 0.61-1.65, p = 0.98). Among unfavorable tumors (simplified grading scale score 5–6), TSA trended toward less visual worsening (OR 0.55, 95%CI 0.28-1.05, P  = .07), more STR/NTR (OR 1.6, 95% CI 1.1-2.33, P  = .014), and had similar local control (HR 1.16, 95%CI 0.67-2.00, p = 0.59) compared to TCA. CONCLUSION: We refined and validated a simplified grading scale for predicting visual outcome and EOR based on TSM pre-operative characteristics. TSA and TCA provide similar outcomes, but TSA trends toward better visual outcomes, although with more STR, among TSM with high simplified grading scale scores.